2009
DOI: 10.1159/000231525
|View full text |Cite
|
Sign up to set email alerts
|

Antiaging Action of Retinol: From Molecular to Clinical

Abstract: The antiaging efficacy of retinol (ROL) has been explored mainly clinically in photoprotected skin sites and for high doses of ROL (0.4–1.6%). The objective of the study was to demonstrate the antiaging action of a low and tolerable dose of ROL (0.1%) ex vivo by measuring the expression of cellular retinoic-acid-binding protein II (CRABP2) and heparin-binding epidermal growth factor (HBEGF) by a histological evaluation of the epidermis and in vivo by assessing major aging signs and performing three-dimensional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 72 publications
4
40
0
Order By: Relevance
“…anti-aging creams) has not produced any harmful effects -apart from the small number of allergic reactions described in several studies [1] . Such findings are not surprising as cosmetic products are developed for continuous long-term application with lower antioxidant concentrations than products intended for medical treatment [46] .…”
Section: Antioxidants In Medical and Cosmetic Treatmentsmentioning
confidence: 97%
“…anti-aging creams) has not produced any harmful effects -apart from the small number of allergic reactions described in several studies [1] . Such findings are not surprising as cosmetic products are developed for continuous long-term application with lower antioxidant concentrations than products intended for medical treatment [46] .…”
Section: Antioxidants In Medical and Cosmetic Treatmentsmentioning
confidence: 97%
“…In a finite element modelling context, it implies that using a single set of mechanical properties for the stratum corneum would limit the domain of validity of the simulation results to specific conditions. A wide array of experimental and clinical measurement techniques are used to characterise particular aspects of skin biology and biophysics (Alexiades-Armenakas, 2007;Batisse et al, 2002;Bellemere et al, 2009;Delalleau et al, 2006;Diridollou et al, 2000;Gunner et al, 1979;Hendriks et al, 2006;Jor et al, 2013;Limbert and Simms, 2013;Tonge et al, 2013a;Tonge et al, 2013b;Wan Abas, 1994). Nevertheless, complementary approaches based on mathematical and computational modelling techniques offer promising avenues to further our understanding of the skin (Areias et al, 2003;Bischoff et al, 2000;Boissieux et al, 2000;Buganza Tepole and Kuhl, 2014;Cavicchi et al, 2009;Duan et al, 2000;Evans, 2009;Flynn and McCormack, 2008a, b;Flynn andMcCormack, 2009, 2010;Hendriks et al, 2006;Hendriks et al, 2003;Kuwazuru et al, 2008;Larrabee and Galt, 1986a, b;Larrabee and Sutton, 1986;Lévêque and Audoly, 2013;Tepole et al, 2014a;Tepole et al, 2014b;Tepole et al, 2011;Zöllner et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…chronological aging. In the past, we have demonstrated that lower concentration of retinol (0.1%) also delivers beneficial result on skin photoaging signs [33,34]. Even more, in the study described in this paper, we have demonstrated that the clinical efficacy of retinol could be achieved with a concentration of retinol as low as 0.04% by using it in combination with a chromone derivative and low molecular weight fragments of hyaluronic acid.…”
Section: Discussionmentioning
confidence: 71%